Chalcogen Bonds in Selenocysteine Seleninic Acid, a Functional GPx Constituent, and in Other Seleninic or Sulfinic Acid Derivatives. Issue 16 (16th July 2021) - Tripathi, Abhishek; Daolio, Andrea; Pizzi, Andrea; Guo, Zhifang; Turner, David R.; Baggioli, Alberto; Famulari, Antonino; Deacon, Glen B.; Resnati, Giuseppe; Singh, Harkesh B.
Abstract: The controlled oxidation reaction of L‐selenocystine under neutral pH conditions affords selenocysteine seleninic acid (3‐selenino‐L‐alanine) which is characterized also by means of single‐crystal X‐ray diffraction. This technique shows that selenium forms three chalcogen bonds (ChBs), one of them being outstandingly short. A survey of seleninic acid derivatives in the Cambridge Structural Database (CSD) confirms that the C−Se(=O)O− functionality tends to act as a ChB donor robust enough to systematically influence the interactional landscape in the solid. Quantum Theory of Atom in Molecules (QTAIM) analysis proves the attractive nature of the short contacts observed in crystals containing the seleninic functionality and calculation of surface molecular electrostatic potential (MEP) reveals that remarkably positive σ‐holes can frequently be found opposite to the covalent bonds at selenium. Both CSD searches and QTAIM and MEP approaches show that also the sulfinic acid moiety can function as a ChB donor, albeit less frequently than the seleninic acid one. These findings may contribute to a better understanding, at the atomic level, of the mechanism of action of the enzymes that control oxidative stress and ROS deactivation and that contain selenocysteine seleninic acid and cysteine sulfinic acid in the active site. Abstract : L‐selenocysteine seleninic acid displays in the solid state three short chalcogen bonds. Analyses of the Cambridge Structural Database and theoretical studies prove that seleninic acid derivatives frequently show the presence of positive σ‐holes and function as robust chalcogen bond donors. Sulfinic acid derivatives behave similarly, but σ‐holes are less positive and chalcogen bonds are formed less commonly.